Confucian moral self cultivation - Ivanhoe, P. J (USA : Hackett Publishing company, 2000)
A concise and accessible introduction to the evolution of the concept of moral self cultivation in the Chinese Confucian tradition, this volume begins with an explanation of the pre-philosophical development of ideas central to this concept, followed by an examination of the specific treatment of self cultivation in the philosophy of Kongzi ("Confucius"), Mengzi ("Mencius"), Xunzi, Zhu Xi, Wang Yangming, Yan Yuan, and Dai Zhen. In addition to providing a survey of the views of some of the most influential Confucian thinkers on an issue of fundamental importance to the tradition, Philip J. Ivanhoe also relates their concern with moral self cultivation to a number of topics in the Western ethical tradition. -- from back cover
Kongzi ("Confucius") -- Mengzi ("Mencius") -- Xunzi -- Zhu Xi -- Wang Yangming -- Yan Yuan -- Dai Zhen
Includes bibliographical references (pages 105-117) and indexes
Keywords: Ethics -- China; Philosophy, Confucian